2015
DOI: 10.5103/kjsb.2015.25.1.077
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lower Limb Muscle Activity on Postural Stability and Ground Type During Gait in Elderly Women

Abstract: Objective : The purpose of this study was to analyze the effects of lower limb muscle activity on postural stability and ground type in elderly women subjects. Results : In the double-support phase, left and right rectus femoris, left biceps femoris, left and right tibialis anterior, and left gastrocnemius did not show a significant difference in postural stability according to ground type. However right biceps femoris and gastrocnemius showed higher muscle activity in the elderly women group with lower postur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…The increased muscle activity in the OT and UT measured when using the RBH is thought to ensure gait stability in environments with obstacles or uneven ground. Our findings are commonly in line with a previous study which found that BF plays an important role in maintaining dynamic postural stability in older adults during walking [30]. It is suggested that the significant decrease in BF activity during the use of the RHH was influenced by the structural characteristics of the walker, which has a lift pedal and relatively large wheels.…”
Section: Discussionsupporting
confidence: 93%
“…The increased muscle activity in the OT and UT measured when using the RBH is thought to ensure gait stability in environments with obstacles or uneven ground. Our findings are commonly in line with a previous study which found that BF plays an important role in maintaining dynamic postural stability in older adults during walking [30]. It is suggested that the significant decrease in BF activity during the use of the RHH was influenced by the structural characteristics of the walker, which has a lift pedal and relatively large wheels.…”
Section: Discussionsupporting
confidence: 93%
“…These vibratory stimuli artificially creates gravitational conditions for aviators in gravity-free space; thus, its original purpose was to prevent functional and morphological degradations of the skeletal system. Studies have shown that vibratory stimulations might have a positive effect on the respiratory, circulatory, nervous, and endocrine systems as well as on the muscle and skeletal systems (Cardinale & Bosco, 2003;Oh, Kang, Min, & Kwon, 2015;Woo & Park, 2015); since then, such stimulations have been expanded to include fields, such as physical therapy and rehabilitation (Remaud, Cornu, & Guével, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…보행각도에 따른 충격의 크기에 대한 연구들은 이루어 져 있지만 (Kwon, 2001;Jung, 2004) 65세 이상 노인들의 33%가 매년 낙상하고 그중 50% 는 다시 낙상한다고 보고되고 있다 (Moreland et al, 2003). 주로 보행 시 발생하는 낙상 문제는 노인의 균 형 감각과도 밀접한 관련을 있을 뿐 아니라, 노화에 따른 고유수용감각기능의 결여와도 관련이 높다 (Woo & Park, 2015). 노인들의 보행 박자는 크게 변화가 없 지만 (Kerrigan et al, 1998;Cromwell et al, 2001), 노 인들이 같은 수의 걸음걸이로 보다 짧은 거리를 이동 하게 되면서 자연 보장이 짧아지고 보다 안정된 보행 을 위하여 두 발이 지면에 있는 시간은 길어지게 된다 (Cromwell et al, 2001 (Abellan et al, 2009;Abellan et al, 2010;Pamoukdjian et al, 2015).…”
unclassified